2011
DOI: 10.1590/s0101-31222011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes de Passiflora setacea e dormência induzida pelo armazenamento

Abstract: RESUMO -Objetivou-se nesse trabalho avaliar a germinação inicial de sementes de Passiflora setacea DC com diferentes níveis de umidade e após a conservação sob diferentes temperaturas. Foram utilizados tratamentos pré-germinativos com nitrato de potássio (KNO 3 ) e ácido giberélico (GA 3 ). A germinação foi conduzida em papel germitest embebido em água. O teste de tetrazólio foi empregado para verificar a viabilidade das sementes após os períodos de armazenamento. Foi possível verificar que: (i) as sementes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…Researches with sunflower seeds have shown that storage at low temperatures (10 °C) occasioned the maintenance of seed quality compared with those stored at 25 °C, but the reduction in germination occurred independent of temperature after three months of storage (Abreu et al, 2011). Passiflora setacea seed maintains viability when stored at subzero temperatures for three months, but after the eighth month of storage the seeds not treated with gibberellic acid do not germinate and those treated with GA3 showed very low germination (3-15%) (Pádua et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Researches with sunflower seeds have shown that storage at low temperatures (10 °C) occasioned the maintenance of seed quality compared with those stored at 25 °C, but the reduction in germination occurred independent of temperature after three months of storage (Abreu et al, 2011). Passiflora setacea seed maintains viability when stored at subzero temperatures for three months, but after the eighth month of storage the seeds not treated with gibberellic acid do not germinate and those treated with GA3 showed very low germination (3-15%) (Pádua et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the lack of reference of TZ staining patterns for Passiflora makes it difficult to evaluate the results. In some studies in which the TZ test was performed to evaluate the viability of Passifloraceae seeds, such as in P. alata (Zucareli et al, 2003;Ferreira et al, 2005) and P. setacea (Pádua et al, 2011), no images were provided that could be used for comparison with other species, such as in the present study (P. foetida var. glaziovii).…”
Section: Discussionmentioning
confidence: 99%
“…When the hard seeds of P. alata were evaluated by the TZ test to determine the percentage of dormant and damaged seeds, viable seeds showed red or pink staining, whereas unviable seeds were milky-white or red (Zucareli et al, 2003). Pádua et al (2011) evaluated the seeds of P. setacea and observed that viable seeds showed pinkish colouration in at least half of the cotyledons and throughout the embryonic axis. These examples highlight the importance of standardisation and comparison between staining results.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the differences within species, there are differences between distinct accessions or cultivars in the same species (ALEXANDRE et al, 2004). Several other factors also influence seed germination and storage, including quality and physiological maturity (NEGREIROS et al, 2006), presence or absence of dormancy (PÁDUA et al, 2011;SANTOS et al, 2012a;REGO et al, 2014) and different methods of seed extraction, processing and storage (PEREIRA e DIAS, 2000;OSIPI et al, 2011;MELETTI et al, 2007;PÁDUA et al, 2011).…”
Section: Germination and Seed Storagementioning
confidence: 99%